DAMPAK PERTAMBAHAN JUMLAH PENDUDUK DAN INVESTASI TERHADAP PERTUMBUHAN PENDAPATAN PER KAPITA DI INDONESIA : Studi Kasus 34 Provinsi - Sudarlan Sudarlan (Politeknik Negeri Samarinda, 2019)
In the era of decentralization that has been enacted by the government of Indonesia in 2000, where the most central government authority delegated to provincial and district/city governments, specialized for financial management and policy areas to encourage the development of the region, that is improving the welfare of the societies measured by the per capita income for the community.The purpose of this research is to understand the affect of population, investment and inflation to per capita income growth by 33 provincial data in Indonesia from 2002 to 2011. The research used explanatory method by using time-series and cross-section data and applied an Ordinary Least Square method (OLS).The important finding in this research is (a) the number of population had a negative impact and significant statistically on per capita income growth, (b) the number of investment had positive impact and significant statistically on per capita income growth, and (c) inflation did not have any impact on per capita income growth. Keywords: per capita income growth, population, inflation, investment and Indonesia